Penerapan Sanksi Pidana Adat Perzinaan di Nagari Koto Tinggi Berdasarkan Hukum Adat Salingka Nagari - Harfiani, Putri Salsa; Zurnetti, Aria (Fakultas Hukum Universitas Andalas, 2025)
Customary law in Indonesia is recognized by the state, even though it is unwritten, and it develops from community customs governed by norms passed down through generations. This is stipulated in Articles 18B and 28I of the 1945 Constitution. Customary criminal law regulates offenses with sanctions such as fines, expulsion, or other punishments, as seen in the Minangkabau customary law related to criminal acts such as adultery. The resolution of customary criminal cases is carried out through deliberation and supervision by customary leaders. In Minangkabau, customary criminal law is known as